Viking worlds : things, spaces and movement - Eriksen, Marianne Hem (Oxbow Books, 2014)
Fourteen papers explore a variety of inter-disciplinary approaches to understanding the Viking past, both in Scandinavia and in the Viking diaspora. Contributions employ both traditional inter- or multi-disciplinarian perspectives such as using historical sources, Icelandic sagas and Eddic poetry and also specialised methodologies and/or empirical studies, place-name research, the history of religion and technological advancements, such as isotope analysis. Together these generate new insights into the technology, social organisation and mentality of the worlds of the Vikings.Geographically, c.